2023
DOI: 10.7759/cureus.35339
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Awareness of Parents Attending Pediatric Clinic Regarding Pediatric Obstructive Sleep Apnea in Jeddah: A Cross-Sectional Study

Abstract: Background: Obstructive sleep apnea (OSA) is characterized by chronic, recurrent episodes of partial or complete airway obstruction during sleep. It has a negative impact on quality of life and behavior and can lead to adverse neurological and cardiovascular outcomes if left untreated. This study aims to assess the awareness and knowledge of pediatric OSA among parents attending a general pediatric clinic in Jeddah, Saudi Arabia.Methods: An observational cross-sectional study was conducted from October 2022 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 17 publications
7
5
0
Order By: Relevance
“…In our study, we found that restless sleep, mouth breathing, and snoring were the most reported symptoms. These findings are consistent with previous studies by Alosaimi et al and Bashir et al However, our study showed a significantly higher correct response rate compared to Bashir et al's study [ 7 , 8 ]. Our findings also revealed that bedwetting and hyperactivity were poorly recognized by the parents, similar to the results of studies conducted by Alosaimi et al and Xu et al [ 8 , 10 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In our study, we found that restless sleep, mouth breathing, and snoring were the most reported symptoms. These findings are consistent with previous studies by Alosaimi et al and Bashir et al However, our study showed a significantly higher correct response rate compared to Bashir et al's study [ 7 , 8 ]. Our findings also revealed that bedwetting and hyperactivity were poorly recognized by the parents, similar to the results of studies conducted by Alosaimi et al and Xu et al [ 8 , 10 ].…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, the least recognized risk factors were sickle cell disease, diabetes mellitus, Down syndrome, low birth weight, and cerebral palsy. These findings were consistent with the Alosaimi et al study but contradicted the findings of the Bashir et al study, which reported better recognition of these risk factors [ 7 , 8 ]. One possible explanation for this discrepancy is that our study and the Alosaimi et al study were both conducted in Jeddah, while the Bashir et al study was conducted across Saudi Arabia [ 7 , 8 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similarly, a study conducted among women in Jeddah, Saudi Arabia, found that despite positive attitudes toward BSE, this method has performed poorly [10]. Therefore, there is still a need for early detection of breast cancer in Saudi Arabia and to understand the factors affecting BSE.…”
Section: Introductionmentioning
confidence: 99%